The Effect Of Taxation Knowledge, Tax Sanctions And Quality Of Service On Compliance Underground Water Tax - L.G.P. Sri Eka JAYANTI; I.B. Putra MANUABA; I. K. Puja Wirya SANJAYA (Indonesia Strategic Sustainability, 2020)
One of the potential regional revenues is local taxes. Based on the Regional Regulation of the City of Denpasar No. 6 of 2010, that groundwater tax is an important source of regional income to finance the implementation of regional government and improve services to the community. One way to increase government revenue from the tax sector is to increase taxpayer compliance itself. Therefore, it is important for the government to pay attention to the factors that affect taxpayer compliance. The purpose of this study was to determine whether the knowledge of taxation, tax sanctions, and service quality affects the compliance of groundwater taxpayers at the Denpasar City Regional Revenue Agency. Respondents in this study were 89 people. The sampling technique in this study used simple random sampling. The data analysis technique used in this study is multiple linear regression analysis processed with the help of the SPSS software program. Based on the results of the analysis, it was found that knowledge of taxation, moral tax sanctions, and service quality had a positive and significant effect on the compliance of groundwater taxpayers at the Denpasar City Regional Revenue Agency.